The Effect of Cigarette Smoking on Serum Liver Enzymes in Baghdad - Turki, Wasan Qasim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Smoking is the most noticeably horrible human conduct; it is rehearsed by individuals dependent on nicotine numerous hurtful sicknesses, for example, cancer and liver disorder are brought about by smoking cigarettes. So this study aimed to study some of the liver function represented by the enzymes aspartate aminotransferase (AST or GOT) and alanine aminotransferase (ALT or GPT) in smokers and non-smokers for 50 persons in a group consists of 25 smokers and 25 non-smokers of different ages and to study the effectiveness of cigarette smoking on liver enzymes by checking the secretion of (AST) (35.84Â± 4.1)U/ 1 (ALT)(51.08Â±7.286 ) U/1(p